Особливості діагностики сформованості готовності майбутніх офіцерів Міністерства внутрішніх справ до охорони і забезпечення громадського порядку - Швець, Д. В.; Shvets, D. V.; ORCID: http://orcid.org/0000-0002-1999-9956; ResearcherID: B-9071-2018 (Вісник Національної академії Державної прикордонної служби України. - 2014. - Вип. 2, 2014)
У статті подано результати розробки й обґрунтування критеріїв і показників сформованості готовності майбутніх офіцерів до охорони та забезпечення громадського порядку. Визначено і розкрито зміст високого, середнього та низького рівнів сформованості цієї готовності.

The paper presents the results of development and justification of criteria and indicators formation of future officers to protect and maintain public order. The content of high, medium and low levels formation of readiness are determined. Priority lines of higher education development in the conditions of cardinal changes in all state institutions are the search of effective ways for increasing of future officers’ readiness level at executing their principal functions and professional aims. One of such aims is the protection and maintenance of public order as a component of law enforcing system activity for guaranteeing national security of the state and society. In order to clear up the state of future officers’ formed readiness at protecting and maintaining of public order we have carried out the selection of necessary pedagogical tools, we have also analysed a number of scientific researches on issue of choice of criteria and indexes for future officers’ formed readiness at realizing their professional activity and forming important professional internals. The goal of the article is the development and theoretical grounding of criteria and indexes by means of which it will be possible to define future officers’ levels of formed readiness at protecting and maintaining of public order. The results of our research have allowed drawing a conclusion that the choice of criteria for the estimation of formed readiness at protecting and maintaining of public order is the most important precondition for its functionality and is grounded on the necessity to determine a level of future officers’ knowledge and mastering of necessary professional abilities and skills. Therefore at developing of these criteria we took into account both traditional requirements for the criteria, basic approaches in determination of indexes and classification of the criteria, and the newest approbated methods of forming of criteria and indexes. In order to clear up and ground the criteria, indexes and levels of formed readiness at protecting and maintaining of public order we have investigated and analysed theoretical approaches of this range of problems, and the general conclusion of empiric data has been drawn taking into account the special features of training of future officers of the Ministry of Internal Affairs. By means of the developed diagnostic tools it seems possible not only to define the level of formed readiness at protecting and maintaining of public order but also at the same time to estimate objectively effectiveness of the work for realization of aims of our research from its purposeful formation.

В статье представлены результаты разработки и обоснования критериев и показателей сформированности готовности будущих офицеров к охране и обеспечению общественного порядка. Определено и раскрыто содержание высокого, среднего и низкого уровней сформированности этой готовности.
Особенности диагностики сформированности готовности будущих офицеров Министерства внутренних дел к охране и обеспечению общественного порядка
Diagnostic Features formation of readiness of the future officers of the Ministry of Internal Affairs to protect and maintain public order
Швець Д. В. Особливості діагностики сформованості готовності майбутніх офіцерів Міністерства внутрішніх справ до охорони і забезпечення громадського порядку [Електронний ресурс] / Д. В. Швець. // Вісник Національної академії Державної прикордонної служби України. - 2014. - Вип. 2. - Режим доступу: http://nbuv.gov.ua/UJRN/Vnadps_2014_2_14
Швець Д. В. "Особливості діагностики сформованості готовності майбутніх офіцерів Міністерства внутрішніх справ до охорони і забезпечення громадського порядку." Вісник Національної академії Державної прикордонної служби України 2 (2014).
Keywords: Освіта. Педагогіка. Education. Pedagogy. Образование. Педагогика; Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Органи внутрішніх справ. Internal affairs agencies. Органы внутренних дел; Internal Affairs Agencies; органы внутренних дел; Психологія. Рsychology. Психология; готовность к профессиональной деятельности; готовність до професійної діяльності; формування готовності до охорони і забезпечення громадського порядку; development of readiness to ensure public safety and order; формирование готовности к охране и обеспечению общественного порядка; общественный порядок; public order; громадський порядок; майбутні офіцери МВС; будущие офицеры МВД; future officers of the Interior Ministry